It's a well-known fact that if $A$ an Abelian group and $G$ is a group, then all group extensions of $G$ by $A$ is isomorphic with the group ($A\times G,\,\bullet)$, where the group operation $\bullet$ is

$$(a_1,g_1)\bullet(a_2,g_2) = (a_1+\varphi_{g_1}(a_2)+f(g_1,g_2),\,g_1g_2)\tag{1}$$


  1. $\varphi:(A\times G)\to A: (a,g)\mapsto \varphi_g(a)$ is a group action of $G$ on $A$
  2. $f: G\times G\to A$ is a cocycle, i.e. satisfies $f(g_1,\,g_2g_3)+\varphi_{g_1}(f(g_2,\,g_3)) = f(g_1g_2,\,g_3)+f(g_1,\,g_2)$.

I'd like to compute the inverse element of $(a,g)$. For the sake of simplicity, let's take a normalized $f$, that is, for the identity element $e$ of $G$ suppose $f(e,e)=0$. In this case, $$f(g,e)=f(e,g)=f(e,e)=0\tag{2}$$ for all $g\in G$ (where $0$ is the identity element of $A$), and the identity element of $(A\times G,\bullet)$ is $(0,e)$. So, if $(a,g)^{-1}=(a_1,g_1)$ then $$ (a_1,g_1)(a,g) = (0,g)\tag{3}$$ and $$ (a,g)(a_1,g_1) = (0,g)\tag{4}$$ From (1), (2) and (3) $$g_1=g^{-1}$$ and $$a_1=\varphi_{g}(a)-f(g^{-1},g)\tag{5}$$ while from (1), (2) and (4) $$ a_1=\varphi_g(a)+\varphi_g(f(g,g^{-1}))\tag{6}$$

From the equality of the RHS of (5) and (6)


Is it sure that this holds for every normalized 2-cocycle? I couldn't derive this from the cocycle condition

$$ f(g_1,g_2g_3)+\varphi_{g_1}(f(g_2,g_3)) = f(g_1g_2,g_3) + f(g_1,g_2)\tag{8}$$ Perhaps I missed something?


1 Answer 1


(I think in (3) and (4), the "$(0,g)$" should be "$(0,e)$".)

I am not sure how you are getting (5) and (6). Using (1) and (3), I get \begin{align} a_{1}+\varphi_{g^{-1}}(a) + f(g^{-1},g) = 0 \tag{5$'$} \end{align} and using (1) and (4), I get \begin{align} a+\varphi_{g}(a_{1}) + f(g,g^{-1}) = 0 \tag{6$'$} \end{align} and applying $\varphi_{g^{-1}}$ to (6') gives \begin{align} \varphi_{g^{-1}}(a)+a_{1} + \varphi_{g^{-1}}(f(g,g^{-1})) = 0 \tag{6$''$} \end{align} and comparing (5') and (6'') gives \begin{align} f(g^{-1},g) = \varphi_{g^{-1}}(f(g,g^{-1})) \tag{7$'$} \end{align} which you can get by setting $(g_{1},g_{2},g_{3}) = (g^{-1},g,g^{-1})$ in (8) and using (2).


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.